Malacofauna from Cappa Lombo Site: Environmental Reconstruction and Subsistence Strategies of The Bontocani Highland Karst Region, South Sulawesi - Restu Budi Sulistiyo; Fakhri (KALPATARU, 2023)
The remains of mollusk shell fragments are ecofacts that can explain the environmental conditions occupied by humans, especially in the context of the Holocene period in Sulawesi. This research answers questions related to the types of mollusks found in the cultural layer and aims to identify malacofauna remains at the Cappa Lombo site, Bontocani, South Sulawesi. The data collection method was carried out through excavation, and the analytical method involved taxonomic identification, external morphological identification, taxonomic classification, and documentation. This study successfully identified 10 families consisting of 15 genera and species. Terrestrial gastropod mollusks consist of the families Alycaeidae, Cyclophoridae, Ariophantidae, Dyakiidae, Clausiliidae, Achatinidae, and Camaenidae. Freshwater gastropods consist of 2 families, namely Pachychilidae and Viviparidae, while the bivalve class is only represented by the Cyrenidae family, which inhabits estuaries. Based on this identification, this research shows that the reconstruction of the environmental conditions around this site indicates a wet rainforest environment, which tends to be covered with vegetation and primary tropical forest. Additionally, during the occupancy period, there was a change in land use around this site. Data on the presence of mollusks also indicate consumption. Although mollusks were not a primary dietary source, humans during the Holocene at this site were able to utilize the aquatic environmental resources around the site they inhabited.